Effectiveness of photodynamic therapy on the treatment of chronic periodontitis: a systematic review during 2008–2023 - Mahdizade Ari, Marzie; Amirmozafari, Nour; Atieh Darbandi,; Afifirad, Roghayeh; Asadollahi, Parisa; Irajian, Gholamreza (Frontiers in Chemistry, 2024)
Objective This study investigated the effect of photodynamic therapy on chronic periodontitis patients and then evaluated the microbial, immunological, periodontal, and clinical outcomes. The significant effects of photodynamic therapy obtained by in vitro and in vivo studies have made it a popular treatment for periodontal diseases in recent years. Photodynamic therapy is a novel bactericidal strategy that is stronger, faster, and less expensive than scaling and root planing. Method This study registered on PROSPERO (CRD42021267008) and retrieved fifty-three randomized controlled trials by searching nine databases (Medline, Embase, Scopus, Open Gray, Google Scholar, ProQuest, the Cochrane Library, Web of Science, and ClinicalTrials.gov) from 2008 to 2023. Of 721 records identified through database searches following title and full-text analysis, and excluding duplicate and irrelevant publications, 53 articles were included in this systematic review. Fifty of the 53 eligible studies fulfilled all the criteria in the Joanna Briggs Institute’s (JBI’s) Checklist for RCTs; the remaining articles met 9–12 criteria and were considered high quality. Results The present study showed that photodynamic therapy in adjunct to scaling and root planing has the potential to improve periodontal parameters such as clinical attachment loss or gain, decrease in bleeding on probing, and probing pocket depth. In addition, photodynamic therapy decreases the rate of periodontal pathogens and inflammation markers, which, in turn, reduces the progression of periodontitis. Conclusion Photodynamic therapy is considered a promising, adjunctive, and low-cost therapeutic method that is effective in tissue repair, reducing chronic periodontitis, reducing inflammation, and well-tolerated by patients.